2019
DOI: 10.1007/s40037-019-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing faculty development impact: A social network analysis

Abstract: Faculty development programs have tended to focus on low levels of evaluation such as participant satisfaction rather than assess the actual changes that training has brought about in the workplace. This has prompted scholars to suggest using social network analysis as a means to provide a more rigorous method of evaluating the impact of faculty development. To test the feasibility of such a suggestion, we used the social network analysis concepts of social cohesion to assess the impact of a year-long fellowsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Future research will include evaluation of the training program and following the careers of AGE-WELL trainees who complete the program, using such methods as social network analysis (Dawson & Hubball, 2014;Foo et al, 2019) to observe the paths they trace within their own discipline and how those intersect with colleagues across disciplinary divides. Such efforts will afford ongoing monitoring of longer-term, public-facing impacts of former AGE-WELL trainees as they help to address the wicked problem of aging gracefully and well.…”
Section: Discussionmentioning
confidence: 99%
“…Future research will include evaluation of the training program and following the careers of AGE-WELL trainees who complete the program, using such methods as social network analysis (Dawson & Hubball, 2014;Foo et al, 2019) to observe the paths they trace within their own discipline and how those intersect with colleagues across disciplinary divides. Such efforts will afford ongoing monitoring of longer-term, public-facing impacts of former AGE-WELL trainees as they help to address the wicked problem of aging gracefully and well.…”
Section: Discussionmentioning
confidence: 99%
“…83 Lastly, while we did not include studies exploring nonhuman relations, our search of the literature suggested that SNA can be used to explore other domains of medical education, such as curriculum design and content integration. 84,85 Focusing on the use of SNA for educational purposes in other areas of health professions education (e.g., dentistry; nursing; rehabilitation sciences) or other aspects of medical education (e.g., faculty development [86][87][88] or continuing professional development 89,90 ) would also be beneficial.…”
Section: Social Network and Educational Considerationsmentioning
confidence: 99%
“…Network analysis can provide insight for a project on the problem or system being defined [67] as well as leadership effectiveness [68] and connections between network patterns and outcomes [69]. It can also be used to identify gaps or tipping points [70], identify learning pathways [71], evaluate impact [72] or some combination of these [67]. Analyzing the strength and centrality of network ties also provides information on the level of stakeholder influence or marginalization, and can identify brokers [73].…”
Section: Domain: Relationship Orientedmentioning
confidence: 99%